THE INFLUENCE OF ISLAMIC EDUCATION ON SHARIA FINANCIAL BEHAVIOR THROUGH ISLAMIC ECONOMIC LITERACY: THE MODERATING ROLE OF RELIGIOSITY - Muh Yusuf Qamaruddin; Hadi Pajarianto; Harun Alrasyid (Institut Agama Islam Al Hidayah Bogor, 2026)
The rapid expansion of digital financial services has increased the importance of promoting Sharia-compliant financial behavior among Generation Z, yet the mechanisms through which Islamic education shapes such behavior remain insufficiently understood. This study investigates the influence of Islamic education on Sharia financial behavior through the mediating role of Islamic economic literacy while examining the moderating role of religiosity. A quantitative research design was employed using a cross-sectional survey of 150 Generation Z respondents in Palopo City, Indonesia. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results indicate that Islamic education has a significant positive effect on Islamic economic literacy, and Islamic economic literacy significantly enhances Sharia financial behavior. However, the direct effect of Islamic education on Sharia financial behavior is not significant, indicating that Islamic economic literacy fully mediates this relationship. Furthermore, religiosity significantly moderates the relationship between Islamic economic literacy and Sharia financial behavior, demonstrating that the influence of financial literacy on behavior varies according to individuals’ levels of religious commitment. The proposed model also exhibits substantial explanatory and predictive power, confirming the robustness of the integrated framework. These findings contribute to the Islamic education and Islamic finance literature by demonstrating that value-based education promotes ethical financial behavior primarily through the development of Islamic economic literacy rather than through direct influence. Practically, the study suggests that educational institutions and policymakers should strengthen Islamic economic literacy within Islamic education curricula while reinforcing religious values to foster sustainable Sharia financial behavior among Generation Z in the digital era.